Peran Hukum Internasional dalam Menyikapi Ketegangan Korea Utara dan Korea Selatan - Dita Pratiwi; Mira Nila Kusuma Dewi; Muhammad Haekal Amri; Arif Andy; M. Sjukri Sopamena; Mahmud Rahim Sopamena; Hilda Fachriza (Media Hukum Indonesia (MHI), 2026)
This study aims to provide an in-depth understanding of legal norms and their application in the tensions between North Korea and South Korea, as well as to integrate various legal sources and scholarly literature as the basis for analysis. The research employs a qualitative method with a normative approach, focusing on the analysis of applicable legal norms, principles, and regulations at both national and international levels. The data are obtained from various sources, including legislation, legal doctrines, academic journals, books, official websites, and relevant international legal instruments. Data analysis is conducted qualitatively through the evaluation, interpretation, and synthesis of legal materials to produce logical and comprehensive legal arguments. The findings indicate that the conflict between North Korea and South Korea constitutes a complex and protracted global security issue, with significant implications for the stability of East Asia and the international legal system. From the perspective of international law, this conflict is not merely a bilateral dispute but represents a serious violation of norms and principles of world peace. The United Nations Security Council has responded by issuing resolutions condemning North Korea’s actions and imposing economic and political sanctions, such as asset freezes and oil embargoes. However, the enforcement of international law faces major obstacles due to North Korea’s non-compliance.